2019
DOI: 10.1002/anie.201912570
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Ultrafast Molecular Permeation through Well‐Defined 2D Nanochannels of Lamellar Membranes

Abstract: Lamellar membranes with well‐defined 2D nanochannels show fast, selective permeation, but the underlying molecular transport mechanism is unexplored. Now, regular robust MXene Ti3C2Tx lamellar membranes are prepared, and the size and wettability of nanochannels are manipulated by chemically grafted hydrophilic (−NH2) or hydrophobic (−C6H5, −C12H25) groups. These nanochannels have a sharp difference in mass transfer behavior. Hydrophilic nanochannels, in which polar molecules form orderly aligned aggregates alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 46 publications
4
59
0
4
Order By: Relevance
“…This was further studied by XRD. The pure MXene membrane displays the (002) peak located at 7.2°, 27 corresponding to a d-spacing of 1.22 nm (Fig. 2g), while 2P/MXene, 3P/MXene and PA/MXene membranes show enlarged nanochannels with sizes of 1.31, 1.35 and 1.65 nm, respectively.…”
mentioning
confidence: 99%
“…This was further studied by XRD. The pure MXene membrane displays the (002) peak located at 7.2°, 27 corresponding to a d-spacing of 1.22 nm (Fig. 2g), while 2P/MXene, 3P/MXene and PA/MXene membranes show enlarged nanochannels with sizes of 1.31, 1.35 and 1.65 nm, respectively.…”
mentioning
confidence: 99%
“…We expect simulation studies to shed more light on the transport mechanisms of MXene-based membranes in the future. In fact, the very recent contributions of Shamsabadi et al [114] and Wu et al [18] on gas and liquid separations, respectively, validate this expectation. Using MD simulations, Shamsabadi et al revealed the crucial role of interfacial interactions between PA blocks of Pebax 1657 and Ti 3 C 2 T x for achieving high CO 2 permeability of resulting MMMs.…”
Section: Simulation/modeling Approachesmentioning
confidence: 85%
“…It is well-established that the flux of incompressible and Newtonian fluids passing through channels made up of 2DMs can be described well by Hagen-Poiseuille law, Equation 3. The utility of Hagen-Poiseuille law for MXene-based membranes have been shown by Wang et al [109] and Wu et al [18] for NLMs, and Wei et al [130] for TFNs. In accordance, the permeance values obtained in both cases were inversely proportionate to the viscosity of the organic solvents tested.…”
Section: Organic Solvent Nanofiltrationmentioning
confidence: 93%
See 1 more Smart Citation
“…The formulas of MXene and MAX are M n+1 X n T x and M n+1 AX n , respectively, in which M refers to early transition metal, X refers to C and/or N, A refers to A-group element, T refers to surface-terminating functional groups, such as oxygen (O), hydroxyl (OH), or fluorine (F) that are attached to the surface M atoms after the etching procedure, and x refers to the number of termination groups. [8,9] Because of their unique properties, such as layered structure and large surface area, tunable surface properties and hydrophilia, and high electrical conductivity, MXene have already shown promising performance in many applications, including energy storage, [10][11][12] electromagnetic interference shielding, [13] functional filler for organic materials, [14] highly efficient transport and separation, [15] catalysis, [16] and so on.However, the inevitable restacking of MXene nanosheets due to the strong van der Waals interaction still limits the ion transport, [17] and reduces the specific surface area and active sites, which will result in significant loss of electrochemical performance. [18,19] Researchers have made efforts to overcome this problem.…”
mentioning
confidence: 99%